Generalization of the Mukhamadiev theorem on the invertibility of functional operators in the space of bounded functions - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We obtain necessary and sufficient conditions of reversibility of the linear bounded operator d m / d t m + A in the space of functions bounded on R.